Psychological well-being of SLE patients: A comprehensive examination of stress, depression, anxiety and quality of life - Pragya Singhal; Priyanka Srivastava; Liza Rajasekhar (PLoS ONE, 2026)
Systemic Lupus Erythematosus (SLE/Lupus) is a chronic autoimmune disease affecting various organs, and associated with challenges in emotion and mood regulation. Despite the increasing prevalence of SLE globally and in India, neuropsychological data remain underrepresented. This study investigates the psychological health and quality of life among Indian SLE patients using self-reported questionnaires on depression, generalized anxiety, trait anxiety, stress, and quality of life. Results indicate a high prevalence of stress, depression, and both generalized and trait anxiety among the SLE patients. Additionally, SLE patients exhibited significantly reduced quality of life (physical well-being, social relationships, and environmental conditions) compared to their healthy counterparts. Disease severity was significantly correlated with patients’ psychological health and quality of life, highlighting the substantial impact of the disease on individual well-being and their daily functioning. Further, cluster analysis revealed that older SLE patients with a homemaker background reported poorer psychological well-being compared with younger patients with a student background, highlighting the importance of demographic factors in understanding the SLE heterogeneity. In sum, poorer psychological well-being across demographic groups underscores the need for future research examining ethnic diversity within India and for translating these findings into holistic medical plans aimed at improving patients’ quality of life.